Which visual sight skill tested and developed the interaction between central and peripheral vision case duels dribbling soccer skills - Mohammed, Z. (International Journal of Applied Exercise Physiology, 2016)
The present paper analyses the effects of visual keep sight to test and develop the interaction between central and peripheral vision the case of duels dribbling among soccer under 17 years. Where This research aims to propose a method evaluating and coaching this skill in the absence of laboratory tests and virtual visual exercises as a way for Algerian coaches to control the progress of their players. From the principle that the team which wins the most duels has the best chance of winning the game. [1] Our research supports the hypothesis which confirms in one hand that Dynamic visual acuity is the combine between Peripheral and Central vision to have one eye on the ball and the other on the defined [2] . While some authors confirm that the Top-class football players do not watch their steps, but dribble with their heads up [3]. Whereas Previous studies confirm estimate of distance ball foot player is the strategy to master this skill [4] which requires the involvement of the commitment of peripheral vision for information and central vision to master the ball [5]. From the proof and results statistics applied in the current study, we confirm that narrow spaces require the interaction of central vision than peripheral vision. Otherwise, free spaces require peripheral vision than the central vision. Which leaves us to confirm that peripheral vision in the limited space [6] can suffer because the player needs to pay close attention to each contact with the ball [7].